Pengaruh Kepengawasan dan Kepemimpinan Distributif-Relasional Terhadap Komitmen Organisasi Kepala Sekolah Dasar di Kabupaten Semarang - Sophia Tri Satyawati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
The purpose of this study is to uncover the influence of supervision and distributive-relational leadership on the organizational commitment of principals. The method used in this study uses quantitative methods. The population in this study was the principal of Elementary School in Semarang District numbering 510. The sample in this study was determined based on a cluster sampling technique of 127 people. Data collected through a questionnaire that has been tested for validity and reliability. The data analysis technique uses path analysis with SPSS 21 software. The results of the study show that: (1) positive and significant supervision directly influences the principal's organizational commitment; (2) distributive-relational leadership positively and significantly directly influences the organizational commitment of the principal; and (3) supervision positively and significantly influences indirectly through distributive-relational leadership to the commitment of the principal's organization.